PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE PEER LESSON TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 SUNGAI LIMAU KAB. PADANG PARIAMAN - Putri Netris, Zita; Zulfaneti, Zulfaneti; sovia, Anny (Pendidikan Matematika, 2014)
Â ABSTRACTThis research aimed to know understanding the mathematic concept of students XI grade IPA in SMAN 1 Sungai Limau Kabupaten Padang Pariaman by using active learning Strategy tipe peer lesson is better than conventional learning. The type of this research is experimental research by design randomized subject. The population of this research is students of XI grade IPA in SMAN 1 Sungai Limau . The technique taked the sample is random, as an experimental class XI IPA1 and a control class XI IPA3. Istruments used in the study is final test in the form of essays. Tne Data obtained in the analysis by using a normality test, homogeneity test and t-test. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at the level of Î± = 0,05 and the results obtained from testing the hypothesis P-value = 0,003 means less than Î± = 0,05, the hypothetical in this study received. So by applying active learning strategy tipe peer lesson is better than the students understanding matematic concept with conventional learning students of XI grade IPA in SMAN 1 Sungai Limau Kabupaten Padang Pariaman 2013/2014 school year with a 95% confidence level.